Investigation of nasal Staphylococcus aureus carriage by real-time PCR in patients receiving hemodialysis treatment - Çetik Yıldız, Songül; Demir, Cemil (The European Research Journal, 2023)
Objectives: Staphylococcus aureus, coagulase-negative staphylococci (CoNS), and methicillin-resistant S. aureus (MRSA), which are significant nosocomial pathogens, have become a growing global problem because their carriage and diseases have become resistant to many antibiotics. This study aimed to investigate and determine the rate of MRSA carriage among patients receiving hemodialysis treatment using molecular methods. Methods: In the 254 hemodialysis patients, the nasal carriage rates, susceptibility and resistance to S. aureus, CoNS and MRSA were examined using culture and real-time PCR methods. Nasal samples from hemodialysis patients were examined using real-time PCR. Microscopic examination was performed using the Gram staining method, and S. aureus was identified using catalase and coagulase. The strains were then tested for antibiotic susceptibility. Staphylococci was isolated from 231 of the 254 patients. Results: S. aureus carriage was detected in 50 patients, MRSA in 16, methicillin-susceptible S. aureus (MSSA) in 33, CoNS in 66, methicillin-resistant CoNS (MR-CoNS) in 38, and methicillin-susceptible CoNS (MS-CoNS) in 28. S. aureus and MRSA strains exhibited 100% susceptibility to nitrofurantoin, and vancomycin. MSSA strains showed the highest susceptibility to chloramphenicol, clindamycin (84.8%), and co-trimoxazole (36.4%). CoNS showed 100% susceptibility to vancomycin, and 16.7% susceptibility to ampicillin. Vancomycin was found to be the most effective antibiotic against S. aureus, CoNS, and MRSA pathogens identified in patients undergoing hemodialysis, whereas penicillin resistance was found. Conclusions: It can be concluded that one of the most effective ways to prevent the formation of antibiotic resistant strains is the hygiene of the hospital and hospital staff. Real-time PCR is very important for analyzing with high sensitivity.